Parametric modeling and analysis of NFL run plays - Biro, P.; Walker, S. (Journal of Sports Analytics, 2023)
The paper is concerned with the modeling of run plays from data obtained from the NFL. Using a parametric regression model based on the skew-t distribution we estimate the shifts from overall league averages for each team within the NFL. From the interpretation of the parameters we can investigate what the best teams are specifically doing to achieve better performance according to the criterion of average yards per play.